Hybrid toolboxes: Conceptual and empirical analysis of blending patterns in application of hybrid media - Reiss, Michael; Steffens, Dirk (Technological and Economic Development of Economy, 2010)
Hybrid media concepts, i.e. especially combinations of face‐to‐face instruments and electronic media, represent a standard in many fields of application for quite a long time. Such combinations of diverse, and thus hybrid instruments are meanwhile quite commonly used, for example, in marketing, in retail business, for communication in virtual enterprises, in internal communication processes, in human resource development and in higher education. By combining strengths of two or more media and by mutually compensating their weaknesses, hybrid media concepts aim at enhancing performance with respect to effectiveness and efficiency. So far, however, scientific discussion lacks a common understanding of the architecture of hybrid media concepts as well as empirical evidence on the application of hybrid media in practice. Hence, it is unclear to what extent the performance potential of hybrid media concepts is utilized in different application fields and what the drivers of the use and performance of hybrid media concepts are. This article presents and discusses both a conceptualization of hybrid media in terms of diversity, proportions and coupling of hybrid concepts and empirical evidence on hybrid media concepts in two typical application fields: internal communication in change management and blended learning in higher education.Article in English.Hibridinės žiniasklaidos modelių taikymo konceptuali ir empirinė analizėSantrauka. Jau gana seniai hibridinė žiniasklaida, t. y. tiesioginio bendravimo priemonės ir elektroninė žiniasklaida, paplitusi daugelyje veiklos sričių. Ivairūs hibridines žiniasklaidos priemonių deriniai dažnai naudojami marketinge, mažmenineje prekyboje, virtualiujų įmonių veikloje, vidaus komunikacijos procesuose, žmogiškuju išteklių plėtros ir aukštojo mokslo srityse. Derinant dvi ar daugiau žniasklaidos priemones, sustiprinami jų privalumai ir kompensuojami trūkumai. Taigi hibridine žiniasklaida yra veiksmingesnė. Tačiau iki šiol trūksta mokslines diskusijos apie hibridines žiniasklaidos koncepcijas, ju praktinį taikymą. Taigi nera aišku, kokiu mastu naudojamos hibridinės žiniasklaidos priemonės ir kas yra ju naudotojai. Straipsnyje pateikiamos hibridines žiniasklaidos koncepcijos ir ju praktinio taikymo pavyzdžiai vidaus ryšiu valdymo ir aukštojo mokslo srityse.Reikšminiai žodžiai: hibridinės žiniasklaidos koncepcijos, hibridinio valdymo koncepcijos, mišrūs mokymąsis, elektroninis komunikavimas, pokyčių valdymas, e. mokymasis, aukštasis mokslas.First published online: 21 Oct 2010